DAMPAK GENANGAN AIR TERHADAP KERUSAKAN JALAN DI JL. UDARA BERASTAGI - SIMPANG DESA SEMANGAT, DUSUN IV KOTA BERASTAGI - Parada Afkiki Eko Saputra; Fatmila Fatmila (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2023)
Abstract This study aims to determine and analyze road damage due to waterlogging that occurred in Berastagi City and aims to provide alternative solutions for handling road surface damage in accordance with road damage conditions in the field. Road section. Air currently has roads that are prone to waterlogging, especially at the intersection of Selamat village, hamlet IV, Merdeka sub-district, Karo district. Puddles that occur due to drainage that is not functioning properly and even has no drainage at all. High rainfall has resulted in road sections being damaged which has an impact on the inconvenience of road users passing on these roads, causing traffic jams. Based on the identification of problems at the research location, it is known that there are at least four problems that cause puddles on the road surface, namely relatively high rainfall, poor drainage system, vehicles carrying loads exceeding road capacity, and inappropriate land use around the road. its allotment. This research was conducted using qualitative methods, this method emphasizes more on facts in the field and utilizes existing literature as supporting material. The results of this study indicate that the Berastagi Airway - Simpang Spirit Village, Hamlet Iv, Berastagi City suffered quite severe damage at several points. The results of the analysis in the field show that the problem of standing water that occurs on roads is caused by poor drainage conditions. An alternative solution to standing water is to give advice and discipline the people who use the catchment area as agricultural land or housing so that flowing water can be better absorbed. In addition to aspects of financing policy and maintenance management, it also needs the support of various related parties, including road user stake holders, so they can understand the capabilities and carrying capacity of infrastructure and take responsibility for maintaining it for the sake of continuity of service that provides a sense of security, comfort and dignity to these road users.